Preparation method of biomimetic nickel-titanium-magnesium heterostructure as medical implant

By infiltrating the magnesium liquid into the pores of the bionic nickel-titanium structure, the bionic nickel-titanium heterostructure was solved, and the problems of weak binding force and poor mechanical stability in the preparation of existing titanium-magnesium heteromaterials were achieved, and the trade-off between high strength and low modulus was achieved, and mechanical support was maintained after magnesium degradation.

CN119326948BActive Publication Date: 2025-03-25JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411874623.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The preparation of existing titanium-magnesium heterogeneous materials has problems such as weak binding force, uneven distribution and poor mechanical stability after degradation, and it is difficult to obtain a trade-off between high strength and low modulus.

Method used

The bionic nickel-titanium structure is combined with magnesium, and the molten magnesium liquid is penetrated into the pores of the bionic nickel-titanium structure through pressure-free impregnation method to prepare a bionic nickel-titanium-magnesium heterostructure.

Benefits of technology

The close bonding and uniform distribution of nickel-titanium alloy and magnesium materials is achieved, the strength and structural stability of the material are improved, the bioinergic and stress shielding problems are solved, and it still has reliable mechanical support after degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326948B_ABST
    Figure CN119326948B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bionic nickel-titanium-magnesium heterostructure as a medical implant, relates to the technical field of medical implants, and comprises the following steps: step one: completing the establishment of a bionic nickel-titanium monomer structure model based on 3D modeling software, arraying the designed bionic nickel-titanium monomer structure model twice along the x-axis, y-axis and z-axis directions to obtain a bionic nickel-titanium structure model; step two: converting the bionic nickel-titanium structure model designed in step one into an STL format file and importing it into magics software, and printing nickel-titanium alloy powder into a bionic nickel-titanium structure based on a selective laser melting technology; step three: polishing the bionic nickel-titanium structure with a chemical polishing liquid, then ultrasonically treating it under alcohol immersion to remove powder adhered to the surface, combining the bionic nickel-titanium structure with molten magnesium by a pressureless infiltration method, and preparing a bionic nickel-titanium-magnesium heterostructure; step four: implanting the bionic nickel-titanium-magnesium heterostructure into a bone defect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical implants, and in particular to a method for preparing a bionic nickel-titanium-magnesium heterostructure as a medical implant. Background Art

[0002] As a type of titanium alloy, nickel-titanium alloy is considered a potential material in the field of bone implants because it has a low elastic modulus and excellent large deformation recoverability compared to other titanium alloys (TC4), and its own superelasticity and shape memory properties contribute to stability after implantation. In addition, a reasonable porous design for nickel-titanium alloy can also alleviate the "stress shielding" problem. However, titanium alloys have the problem of biological inertness after being implanted in the human body, that is, the nickel-titanium alloy material itself cannot effectively induce bone tissue growth.

[0003] Magnesium and magnesium alloys have become a kind of biomedical material with broad development prospects due to their low elastic modulus (41~45GPa), good bone integration and degradability. Moreover, magnesium is one of the constant elements in the human body, participates in multiple metabolic processes in the body, promotes calcium deposition, and is an essential element for bone growth. However, magnesium (magnesium alloy) has poor corrosion resistance. After being implanted in the human body, the body fluid environment will corrode the material itself during its service life, causing the material to lose stability. In addition, the low strength of magnesium itself has become the biggest bottleneck restricting its development.

[0004] Titanium-magnesium heterogeneous materials refer to new materials that fuse titanium (titanium alloy) and magnesium (magnesium alloy) together to give full play to the respective advantages of the two materials. The preparation of existing titanium-magnesium heterogeneous materials includes powder sintering, pressureless infiltration and hot isostatic pressing, but most of them have problems such as weak bonding, uneven preparation distribution, and poor mechanical stability after degradation. Therefore, the preparation process should be improved to increase the interfacial bonding force to improve the strength requirements of the titanium-magnesium heterogeneous materials themselves; secondly, the ratio of titanium alloy materials and magnesium should be controlled so that the material can achieve a balance between high strength and low modulus, and ensure that it can still meet the service strength requirements after degradation. Summary of the invention

[0005] In view of the shortcomings of the background technology, the present invention aims to develop a biomedical material with low elastic modulus, high strength, load-bearing function in the human body and good biocompatibility; a bionic nickel-titanium structure with a low elastic modulus is designed based on the beetle microstructure in nature, and is combined with magnesium with good bone integration and bone inductivity. Through optimized treatment, molten magnesium liquid is infiltrated into the pores of the bionic nickel-titanium structure by a pressureless infiltration method to obtain a bionic nickel-titanium-magnesium heterostructure.

[0006] To achieve the above solution, the present invention proposes the following technical solution:

[0007] A method for preparing a bionic nickel-titanium-magnesium heterostructure as a medical implant comprises the following steps:

[0008] Step 1: The bionic nickel-titanium monomer structure model is established based on 3D modeling software. The designed bionic nickel-titanium monomer structure model is arrayed twice along the x-axis, y-axis and z-axis directions to finally obtain the bionic nickel-titanium structure model. The porosity of the bionic nickel-titanium structure model is between 45% and 75%;

[0009] Step 2: Convert the bionic nickel-titanium structure model designed in step 1 into an STL format file and import it into the magics software, and print the nickel-titanium alloy powder into a bionic nickel-titanium structure based on the selective laser melting technology;

[0010] Step 3: polishing the bionic nickel-titanium structure with a chemical polishing liquid, then ultrasonically treating it while soaking in alcohol to remove the powder adhering to the surface, and then combining the bionic nickel-titanium structure with molten magnesium by a pressureless infiltration method to prepare a bionic nickel-titanium-magnesium heterostructure;

[0011] Step 4: Implant the bionic nickel-titanium-magnesium heterostructure prepared in step 3 into the bone defect.

[0012] Preferably, the bionic nickel-titanium monomer structure model in step one includes a bionic beetle elytra structure model and a bionic beetle symmetrical rib structure model.

[0013] Preferably, the bionic beetle elytra structure model is obtained by a circular array of multiple X-shaped arc plates.

[0014] Preferably, the bionic beetle symmetrical rib structure model is obtained by a plurality of S-shaped twisted rib circular arrays.

[0015] Preferably, the specific method of polishing the bionic nickel-titanium structure with a chemical polishing liquid in step three is:

[0016] The bionic nickel-titanium structure is wrapped with a thin wire and bound to the sample lifting platform. The height of the sample lifting platform is adjusted to make the bionic nickel-titanium structure fully immersed in the chemical polishing liquid in the beaker. The bottom of the beaker is connected to the rotor of the motor. The rotor drives the flow of the chemical polishing liquid in the beaker through its own rotational motion to prevent uneven polishing of the bionic nickel-titanium structure. No particle adhesion will be observed on the surface of the polished bionic nickel-titanium structure, avoiding the inflammation problem caused by the detachment of dust adhered to the bionic nickel-titanium structure as the degradation process proceeds after implantation.

[0017] Preferably, in step 3, the specific method of combining the bionic nickel-titanium structure with the molten magnesium by the pressureless infiltration method is:

[0018] The bionic nickel-titanium structure is placed in a mold in a box-type atmosphere furnace at room temperature, and then molten magnesium at 800-900°C is poured on the bionic nickel-titanium structure. The magnesium liquid in the mold is properly stirred by means of a clamp to assist the magnesium liquid to enter the bionic nickel-titanium structure until the magnesium liquid covers the bionic nickel-titanium structure. Subsequently, a heavy object is used to press on the upper part of the bionic nickel-titanium structure. Under the action of a protective gas, the magnesium liquid relies on its own gravity to continuously infiltrate the bionic nickel-titanium structure until it is completely filled. Finally, the temperature is raised from room temperature to 800°C in the box-type atmosphere furnace and kept warm for 40-60 minutes. The preparation is completed after the box-type atmosphere furnace is cooled.

[0019] Beneficial effects of the present invention:

[0020] Compared with the prior art, the bionic nickel-titanium-magnesium heterostructure prepared by the present invention has a tighter combination of nickel-titanium alloy material and magnesium material, a more uniform distribution, and realizes the effective preparation of a bicontinuous structure, which makes up for the problem of insufficient strength and structural stability of traditional nickel-titanium-magnesium materials, solves the "stress shielding" problem that has been criticized for a long time in clinical medicine, and effectively improves the biological inertness problem of nickel-titanium alloy as magnesium degrades after implantation;

[0021] The bionic nickel-titanium-magnesium heterostructure prepared by the present invention has been verified through performance verification, which confirms that the mechanical properties of the material meet the stiffness requirements of the implant and achieves an effective balance between low modulus and high strength, breaking through the strength and plasticity conflict problem that traditional materials cannot achieve.

[0022] The present invention innovatively draws on the elytra and cuticle of beetles to prepare a bionic nickel-titanium structure, and combines nickel-titanium as a hard phase material with magnesium as a soft phase material. After implantation into the human body, as the magnesium phase degrades, the structure still has reliable mechanical support. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the characterization of different parts of the Chinese giant flat taro;

[0024] Figure 2 It is a schematic diagram of the bionic characteristic principle of the bionic nickel-titanium monomer structure model, the bionic beetle elytra structure model, and the bionic beetle symmetrical rib structure model;

[0025] Figure 3 It is a flow chart of the preparation of the bionic nickel-titanium structure model;

[0026] Figure 4 It is a flow chart for the preparation of biomimetic nickel-titanium-magnesium heterostructure;

[0027] Figure 5 It is a physical picture of the bionic nickel-titanium-magnesium heterostructure;

[0028] Figure 6is a schematic diagram of biomimetic nickel-titanium-magnesium heterostructures with different porosities;

[0029] Figure 7 It is a schematic diagram of the EDS elemental analysis results of the bionic nickel-titanium-magnesium heterostructure;

[0030] Figure 8 This is the XRD phase analysis diagram of the bionic nickel-titanium-magnesium heterostructure;

[0031] Fig. 9 It is a comparison curve of mechanical test results of a bionic nickel-titanium-magnesium heterostructure (size 2a×2b×2c) obtained from a bionic nickel-titanium structure with a porosity of 75% obtained by melting magnesium liquid, a bionic nickel-titanium structure with a porosity of 75% (size 2a×2b×2c), and a pure magnesium structure (size 2a×2b×2c);

[0032] Fig.10 It is a comparison curve of mechanical test results of a bionic nickel-titanium-magnesium heterostructure (size 2a×2b×2c) obtained from a bionic nickel-titanium structure with a porosity of 60% obtained by melting magnesium liquid, a bionic nickel-titanium structure with a porosity of 60% (size 2a×2b×2c), and a pure magnesium structure (size 2a×2b×2c);

[0033] Fig.11 It is a comparison curve of mechanical test results of a bionic nickel-titanium-magnesium heterostructure (size 2a×2b×2c) obtained from a bionic nickel-titanium structure with a porosity of 45% obtained by melting magnesium liquid, a bionic nickel-titanium structure with a porosity of 45% (size 2a×2b×2c), and a pure magnesium structure (size 2a×2b×2c);

[0034] Fig.12 It is a schematic diagram of bone promotion in a bionic nickel-titanium-magnesium heterostructure under a simulated body fluid environment;

[0035] Fig.13 It is the overall preparation and application flow chart of the present invention;

[0036] Fig.14 This is the electron microscope characterization result of the bionic nickel-titanium-magnesium heterostructure.

[0037] In the figure:

[0038] 1: Bionic nickel-titanium structure model; 11: Bionic nickel-titanium monomer structure model; 111: Bionic beetle elytra structure model; 112: Bionic beetle symmetrical rib structure model. DETAILED DESCRIPTION

[0039] See also Figures 1 to 14 As shown, the preparation method of the bionic nickel-titanium-magnesium heterostructure as a medical implant comprises the following steps:

[0040] Step 1: Using an electron microscope to observe the microstructure of beetles in nature, including the elliptical chamber of its elytra and the Brigon structure of the exoskeleton cuticle, the bionic nickel-titanium monomer structure model 11 is established based on the 3D modeling software solidworks, and the designed bionic nickel-titanium monomer structure model 11 is arrayed twice along the x-axis, y-axis and z-axis directions to finally obtain the bionic nickel-titanium structure model 1, and the porosity of the bionic nickel-titanium structure model 1 is between 45% and 75%;

[0041] Step 2: Convert the bionic nickel-titanium structure model 1 designed in step 1 into an STL format file and import it into the magics software, and print the nickel-titanium alloy powder into a bionic nickel-titanium structure based on the selective laser melting technology;

[0042] Step 3: polishing the bionic nickel-titanium structure with a chemical polishing liquid, then ultrasonically treating it while soaking in alcohol to remove the powder adhering to the surface, and then combining the bionic nickel-titanium structure with molten magnesium by a pressureless infiltration method to prepare a bionic nickel-titanium-magnesium heterostructure;

[0043] Step 4: implanting the bionic nickel-titanium-magnesium heterostructure prepared in step 3 into the bone defect;

[0044] Step 5: performing material characterization and phase analysis on the bionic nickel-titanium-magnesium heterostructure prepared in step 4;

[0045] Step 6: Perform performance tests on the bionic nickel-titanium-magnesium heterostructure after material characterization and phase analysis in step 5, and further analyze the test results. The mechanical test is mainly a quasi-static compression test, which is carried out using a universal testing machine with a constant compression rate of 1 mm / min. The biocompatibility test mainly observes the proliferation and ingrowth of bone cells.

[0046] For further information, see Figure 3 As shown, the bionic nickel-titanium monomer structure model 11 in the step one includes a bionic beetle elytra structure model 111 and a bionic beetle symmetrical rib structure model 112; wherein the design of the bionic beetle elytra structure model 111 is inspired by the elliptical chamber structure of the beetle elytra part, and as an external frame, it mainly bears the load and absorbs most of the energy; and the design of the bionic beetle symmetrical rib structure model 112 is based on the rotation characteristics of the Brigan structure of the cuticle part of the beetle exoskeleton, and serves as a filler inside the frame to stabilize deformation.

[0047] For further information, see Figure 3 As shown, the bionic beetle elytra structure model 111 is obtained by a circular array of multiple X-shaped arc plates.

[0048] For further information, see Figure 3As shown, the bionic beetle symmetrical rib structure model 112 is obtained by a plurality of S-shaped twisted rib circular arrays.

[0049] For further information, see Figure 3 As shown, the present invention exemplifies a design method of a bionic nickel-titanium monomer structure model 11, which includes the following contents:

[0050] First, the bionic beetle elytra structure model 111 is optimized and designed based on a regular hexagonal prism. One side is selected, and the four vertices B, C, I, and H of the selected side are used for curvature extension. The original straight columns BH and CI are transformed into two arc beams with a radius of Rf1, and the centers of the arc beams are located at the midpoints of the straight lines BH and CI respectively. At the same time, the original straight columns BC and HI are synchronously transformed into two arc beams with a radius of Rf2, and the centers of the arc beams are located at the midpoints of BC and HI respectively. At the same time, it is ensured that the four arc beams intersect at the face center position W, and then the solid structure model formed at the selected side BCIH is circularly arrayed 6 times along the central axis to ensure that the overall size of the bionic beetle elytra structure model 111 in a closed state after the circular array is the same as that of the regular hexagonal prism.

[0051] A circular outline is drawn based on the vertex B of the regular hexagonal prism, the diagonal point K of the vertex B, and the body center X, and the diameter of the circular outline is r. Then, a lofting operation is performed based on the circular outline to obtain an S-shaped torsion rib. Then, the formed torsion rib is arrayed in a circle along the central axis to ensure that the bionic beetle symmetrical rib structure model 112 obtained after the circular array meets the vertical dimension c.

[0052] The completed bionic beetle symmetrical rib structure model 112 is embedded into the bionic beetle elytra structure model 111, and the intersecting parts are rounded and smoothed to finally form a bionic nickel-titanium monomer structure model 11 with a size of a×b×c=7.44×6.45×6 (mm). Figure 3 The x, y, and z axis directions shown are linearly arrayed once with dimensions a, b, and c to obtain a bionic nickel-titanium structure model 1.

[0053] Furthermore, the nickel-titanium alloy powder (55.8 wt% Ni) used in step 2 is prepared by a gas atomization method, and the particle size of the nickel-titanium alloy powder is 15 to 53 μm.

[0054] Furthermore, the printing parameters used in the selective laser melting technology in step 2 are laser power 125w, scanning speed 600mm / s, scanning spacing 80μm, and scanning layer thickness 30μm. The printing parameters have been proven to have good molding accuracy in previous studies.

[0055] Furthermore, the raw materials of the chemical polishing solution in step three include 22.5 mol / L hydrofluoric acid, 4 mol / L nitric acid and deionized water, and the volume ratio of hydrofluoric acid: nitric acid: deionized water solution is 1:4:5.

[0056] Furthermore, the specific method of polishing the bionic nickel-titanium structure with chemical polishing liquid in the step three is: the bionic nickel-titanium structure is wrapped with a thin wire and bound to the sample lifting platform, and the height of the sample lifting platform is adjusted to make the bionic nickel-titanium structure fully immersed in the chemical polishing liquid in the beaker, and the bottom of the beaker is connected to the rotor of the motor, and the rotor drives the flow of the chemical polishing liquid in the beaker through its own rotational motion to prevent uneven polishing of the bionic nickel-titanium structure. No particle adhesion will be observed on the surface of the polished bionic nickel-titanium structure, thereby avoiding the inflammation problem caused by the detachment of dust adhered to the bionic nickel-titanium structure as the degradation process proceeds after implantation.

[0057] For further information, see Figure 4 As shown, the specific method of combining the bionic nickel-titanium structure with the molten magnesium by the pressureless infiltration method in step three is:

[0058] The bionic nickel-titanium structure is placed in a mold in a box-type atmosphere furnace at room temperature, and then molten magnesium at 800-900°C is poured on the bionic nickel-titanium structure. The magnesium liquid in the mold is properly stirred by means of a clamp to assist the magnesium liquid to further enter the bionic nickel-titanium structure until the magnesium liquid submerges the bionic nickel-titanium structure. Subsequently, a heavy object is used to press on the upper part of the bionic nickel-titanium structure. Under the action of a protective gas (argon gas), the magnesium liquid relies on its own gravity to continuously infiltrate the bionic nickel-titanium structure until it is completely filled. Finally, the temperature is raised from room temperature to 800°C in the box-type atmosphere furnace and kept warm for 40-60 minutes. The preparation is completed after the box-type atmosphere furnace is cooled.

[0059] See also Figure 1 As shown, in step 1, an electron microscope is used to observe the elytra and exoskeleton of the Chinese giant flat beetle (a type of beetle) at different characterization scales. An elliptical cavity structure composed of fibers is observed in the elytra, and this structure has been proven to be an important reason why the beetle has good energy absorption characteristics; a Brigant structure with rotation angle characteristics is observed in the cuticle of the exoskeleton, and this structure has also been proven to be one of the reasons why the beetle can carry loads stably.

[0060] See also Figure 6As shown in the figure, we prepared bionic nickel-titanium structures with a porosity of 45%, a porosity of 60%, and a porosity of 75%. The bionic nickel-titanium structure with too high a porosity cannot guarantee the mechanical strength, and the bionic nickel-titanium structure with too low a porosity cannot ensure the growth of bone cells. According to existing studies, the porosity range of implants should be between 30% and 90%. Therefore, we selected three porosities of 45%, 60%, and 75% for parametric design and obtained three bionic nickel-titanium-magnesium heterostructures. This was used to verify the differences and action rules of different hard phases (nickel-titanium) and soft phases (magnesium) on the mechanical properties of bionic nickel-titanium-magnesium heterostructures.

[0061] See also Figure 7 and Fig.14 As shown, obvious hard phase region (nickel titanium), soft phase region (magnesium) and diffusion region (nickel titanium-magnesium) can be observed in the bionic nickel titanium-magnesium heterostructure at the 20μm scale, and EDS energy spectrum analysis also confirmed the obvious element diffusion phenomenon in the preparation process.

[0062] See also Figure 8 From the XRD phase analysis shown, it can be seen that the nickel element effectively diffuses into the magnesium phase, thereby generating an intermediate phase magnesium-nickel alloy. This further verifies that the interface between the nickel-titanium phase and the magnesium phase is tightly bonded, and the strong bonding force contributes to the further stable load-bearing of the bionic nickel-titanium-magnesium heterostructure.

[0063] See also Fig. 9 , Fig.10 and Fig.11 The mechanical test results show that the bionic nickel-titanium-magnesium heterostructure can exert better mechanical properties than single-component materials (magnesium phase and nickel-titanium phase) at different porosities. It has higher strength than the soft phase (magnesium) and better ductility and stability than the hard phase (nickel-titanium). This can be used as a reference for the strengthening mechanism of the common shellfish nacre (brick-mud structure) in nature in existing studies. In addition, through indicator quantification, we found that as the porosity decreases, the strength of the bionic nickel-titanium-magnesium heterostructure can fluctuate between 283MPa and 518MPa, and its Young's modulus can fluctuate between 1.8GPa and 3.5GPa (much lower than the Young's modulus of both nickel-titanium and magnesium), indicating that the preparation of a bionic nickel-titanium-magnesium heterostructure with high strength and low modulus characteristics can be achieved based on this method.

[0064] At the same time, considering that the magnesium phase will degrade after the bionic nickel-titanium-magnesium heterostructure is implanted in the human body environment, the mechanical properties of the bionic nickel-titanium-magnesium heterostructure will change. Therefore, we counted the mechanical indicators of the bionic nickel-titanium structure under different porosities and found that its compressive strength can fluctuate between 80MPa and 267MPa (2-180MPa is the service strength requirement of the implant), and the Young's modulus can fluctuate between 1.2GPa and 2.4GPa (0.02-20GPa is the Young's modulus range of natural bone). The above indicators show that even after the magnesium phase is degraded, the bionic nickel-titanium structure that will not be destroyed by degradation still has structural integrity, and can provide a stable mechanical support effect until the end of the service life of the implant and new bone tissue is generated.

[0065] See also Fig.12 As shown in Figure 2, the bionic nickel-titanium-magnesium heterostructure not only has the characteristics of low modulus and high strength, but also after being implanted in the human body environment, the degradable element Mg (magnesium) will be decomposed into Mg 2+ (magnesium ions), while promoting Ca 2+ The formation of (calcium ions) accelerates the proliferation of bone cells, reduces the growth and formation cycle of new bone tissue, and the remaining pores of the bionic nickel-titanium structure originally occupied by the magnesium element will guide the bone tissue to grow in, thereby fitting on the bionic nickel-titanium structure until the end of its service life. The new bone tissue is interconnected in the coherent pores of the bionic nickel-titanium structure, and the damaged bone tissue is restored.

Claims

1. A method for preparing a bionic nickel-titanium-magnesium heterostructure as a medical implant, characterized in that: The steps include: Step 1: Based on 3D modeling software, the bionic nickel-titanium monomer structure model (11) is established, and the designed bionic nickel-titanium monomer structure model (11) is arrayed twice along the x-axis, y-axis and z-axis directions to finally obtain the bionic nickel-titanium structure model (1). The porosity of the bionic nickel-titanium structure model (1) is between 45% and 75%; Step 2: Convert the bionic nickel-titanium structure model (1) designed in step 1 into an STL format file and import it into the magics software, and print the nickel-titanium alloy powder into a bionic nickel-titanium structure based on the selective laser fusion technology; Step 3: polishing the bionic nickel-titanium structure with a chemical polishing liquid, then ultrasonically treating it while soaking in alcohol to remove the powder adhering to the surface, and then combining the bionic nickel-titanium structure with molten magnesium by a pressureless infiltration method to prepare a bionic nickel-titanium-magnesium heterostructure; Step 4: implanting the bionic nickel-titanium-magnesium heterostructure prepared in step 3 into the bone defect; The bionic nickel-titanium monomer structure model (11) in step 1 includes a bionic beetle elytra structure model (111) and a bionic beetle symmetrical rib structure model (112); The bionic beetle elytra structure model (111) is obtained by a circular array of multiple X-shaped arc plates; The bionic beetle symmetrical rib structure model (112) is obtained by a circular array of multiple S-shaped twisted ribs; The specific method of combining the bionic nickel-titanium structure with the molten magnesium by the pressureless infiltration method in step 3 is: The bionic nickel-titanium structure is placed in a mold in a box-type atmosphere furnace at room temperature, and then molten magnesium at 800-900°C is poured on the bionic nickel-titanium structure. The magnesium liquid in the mold is properly stirred by means of a clamp to assist the magnesium liquid to enter the bionic nickel-titanium structure until the magnesium liquid covers the bionic nickel-titanium structure. Subsequently, a heavy object is used to press on the upper part of the bionic nickel-titanium structure. Under the action of a protective gas, the magnesium liquid relies on its own gravity to continuously infiltrate the bionic nickel-titanium structure until it is completely filled. Finally, the temperature is raised from room temperature to 800°C in the box-type atmosphere furnace and kept warm for 40-60 minutes. The preparation is completed after the box-type atmosphere furnace is cooled.

2. The method for preparing the bionic nickel-titanium-magnesium heterostructure as a medical implant according to claim 1, characterized in that: The specific method of polishing the bionic nickel-titanium structure with a chemical polishing liquid in step 3 is: The bionic nickel-titanium structure is wrapped with thin wires and bound to the sample lifting platform. The height of the sample lifting platform is adjusted to allow the bionic nickel-titanium structure to be fully immersed in the chemical polishing liquid in the beaker. The bottom of the beaker is connected to the rotor of the motor, and the rotor drives the flow of the chemical polishing liquid in the beaker through its own rotational motion.

Citation Information

Patent Citations

  • Preparation method of 3D printing bionic mandible scaffold based on TPMS design

    CN113768666A

  • Bionic vine esophagus operation auxiliary traction tool based on 4D printing technology and forming method of bionic vine esophagus operation auxiliary traction tool

    CN117982181A